W-shaped solitons in inhomogeneous cigar-shaped Bose–Einstein condensates with repulsive interatomic interactions. (9th April 2019) - Triki, Houria; Zhou, Qin; Liu, Wenjun
Abstract: We analyze the formation and dynamics of W-shaped solitons in an inhomogeneous cigar-shaped Bose–Einstein condensate with repulsive interatomic interactions in the presence of spatially and temporally nonuniform nonlinearity and external potential. The condensate is assumed to have a large number of particles; hence it may be approximated by an effective one-dimensional equation, which is derived from the full three-dimensional Gross–Pitaevskii equation. New classes of W-shaped soliton solutions, which may propagate in the condensate system with the same hump value, are found for the first time by means of the similarity transformation technique. The functional form of these localized nonlinear structures is different from the usual ones reported in the setting of optical fibers. The dynamic behaviors of the W-shaped soliton pulses under different nonlinearity and external potential management that are of particular interest for applications in Bose–Einstein condensates are analyzed.